Entrepreneurship with MindTap: theory, Process,practice - Kuratko, Donald F. (Cengage Learning, 2024)
Presenting the most current thinking in this explosive field, Kuratko's ENTREPRENEURSHIP: THEORY, PROCESS, PRACTICE, 12th EDITION! provides a practical, step-by-step approach that makes learning easy. It incorporates up-to-the-minute information about trending topics such as design innovation, the entrepreneurial mindset, entrepreneurial hustle, bootstrapping, and entrepreneurial coachability. The accompanying MindTap® Learning Suite challenges you to apply what you've learned as you complete a unique set of activities designed to help you sharpen your entrepreneurial skills. You'll tackle activities that challenge you to experience the world of new venture creation or corporate innovation firsthand. This book will be your guide to understanding the entrepreneurial challenges of tomorrow, and MindTap® will teach you the necessary skills to become a leader in the industry.